Microwave field-effect transistors : theory, design, and applications - Pengelly, Raymond S. 1948- (Noble, 1994)
This book covers the use of devices in microwave circuits and includes such topics as semiconductor theory and transistor performance, CAD considerations, intermodulation, noise figure, signal handling, S-parameter mapping, narrow- and broadband techniques, packaging and thermal considerations.